Telepresence and trust: A speech-act theory of mediated communication - Simpson, T (Springer, 2016)
Trust is central to our social lives, in both epistemic and practical ways. Often, it is rational only given evidence for trustworthiness, and that evidence is made available by communication. New technologies are changing our practices of communication, enabling increasing rich and diverse ways of ‘being there’, but at a distance. This paper asks: how does telepresent communication support evidence-constrained trust? In answering it, I reply to the leading pessimists about the possibility of the digital mediation of trust, Philip Pettit and Hubert Dreyfus. I also rebut Media Richness Theory, which proposes a linear relationship between the volume of mediated information and the quality of communication. Positively, I develop a speech-act theory of digitally mediated communication, drawing on Austen’s identification of the illocutionary act. The choice of a particular technology of communication constitutes part of what is communicated, including a setting of the social ‘frame’, and thus the possibilities for trust to be sustained or eroded. How somethign is said is part of what it is that is said.